Curriculum Implementation Index for Geography Learning in East Java, Indonesia - Kurnianto, Fahmi Arif; Pangastuti, Era Iswara; Nurdin, Elan Artono; Wahyuono, Trio (Universitas Negeri Medan, 2024)
Curriculum changes often occur in Indonesia. However, studies regarding the gap between curriculum planning and implementation are still very limited. Therefore, this study aimed to analyze the Curriculum Implementation Index for Geography Learning in East Java. In this study, we used a curriculum implementation index for geography subjects. This study used purposive sampling with several considerations, such as the region distribution of geography teachers and school accreditation. The number of respondents is determined by selecting the person directly related to geography learning and its relation to curriculum implementation. We observed 30 geography teachers to determine curriculum implementation. The curriculum implementation index was used to evaluate consistency between curriculum planning and implementation, as indicated by teachers™ activities and several concepts in geography learning. The results show that the readiness of teachers to implement the curriculum in the laboratory, literature, and media aspects is in the low category. This is indicated by a laboratory index of 1.03, a literature index of 1.58, and a media index of 1.87. This low index means that geography learning does not meet the 2013 curriculum standards, especially in physical geography material, which needs laboratories and media to explain concrete concepts in geography learning. Implementing the 2013 curriculum in geography learning has not met the characteristics of the concrete idea of geography learning, which requires visualization for physical and environmental aspects.Keywords: Curriculum Implementation; Geography Learning; Index; East Java